BOVINE SPONGIFORM ENCEPHALOMYELITIS: sanitary management and damage to the brazilian economy - Davoglio, Lucas Matinato; Junior, Edemar; Vieira, Vanessa Amaro (Revista Interface Tecnológica, 2023)
Bovine Spongiform Encephalomyelitis is a neurological disease that can manifest itself in two ways, the classic and the atypical. It is an incurable disease caused by a Prion that affects ruminants in general. Brazil is a major exporter of beef and suspected cases of the disease could lead the country to suffer embargoes, causing serious damage to the Brazilian economy and the country’s livestock production. The objective of this study is to demonstrate the importance of proper sanitary management in beef cattle as well as the economic impacts caused by Bovine Spongiform Encephalomyelitis (“Mal da Vaca Louca”), so it is very important to better understand the disease and know the importance that the sanitary management exercises under beef cattle production. The justification for this study is to ensure the absence of economic losses and international embargoes related to the production of Brazilian meat. The methodological procedures used were exploratory analysis through literature review, magazine articles and news, where it was considered that the faster the diagnosis, the smaller the economic losses.